IMPLEMENTATION OF DIDACTIC PRINCIPLES IN PRACTICE OF PROPAEDEUTICAL GENERAL TRAINING OF FOREIGN STUDENTS TO STUDY AT THE AVIATION UNIVERSITY - Довгодько, Т. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with the peculiarities of teaching principles realization in the process of pre-university general scientific training of foreign students to studying at technical, specifically, at the Aviation University